2018
DOI: 10.1039/c8tc02507j
|View full text |Cite
|
Sign up to set email alerts
|

Additive engineering to improve the efficiency and stability of inverted planar perovskite solar cells

Abstract: A formamidine acetate salt additive engineering strategy is developed to fabricate perovskite solar cells with high efficiency and stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 60 publications
1
21
0
2
Order By: Relevance
“…During the film formation process, strong interaction between Acand Pb 2+ plays a significant role in the improved quality of resulting perovskite films. Moreover, various previous reports have confirmed that Ac -(in form of PbAc 2, FAAc, MAAc) is engaged in the perovskite growth process, leading to larger grains, and reducing defects [35][36][37] .…”
Section: Introductionmentioning
confidence: 75%
“…During the film formation process, strong interaction between Acand Pb 2+ plays a significant role in the improved quality of resulting perovskite films. Moreover, various previous reports have confirmed that Ac -(in form of PbAc 2, FAAc, MAAc) is engaged in the perovskite growth process, leading to larger grains, and reducing defects [35][36][37] .…”
Section: Introductionmentioning
confidence: 75%
“…It was reported that FAAc controlled the film morphology and improved fill-factor over 80%, which in turn improved PCE to 16.59%. The improved photovoltaic parameter was further associated with the incorporation of FAAc that eliminated the defect and trap density in the MAPbI 3 film and, thus, improved the charge transport efficiency and reduced the hysteresis [98]. On the contrary, methyl ammonium acetate (MAAc) resulted in lower crystallinity and a smaller grain size~200 nm [99].…”
Section: Carboxylic/acid Additivesmentioning
confidence: 99%
“…Benefiting from the advances of various film deposition techniques, such as one-step spin coating [13,21], two-step sequential solution deposition [22,23] and inkjet printing fabrication [24,25], unprecedented progress in the improvement of the efficiency of PSCs has been made. To obtain high-quality perovskite films based on these techniques, researchers control the perovskite morphology by optimizing the solvents for processing [26], varying the annealing temperature [27], adjusting the processing additives [28], sophisticated engineering of the solvent [12,14] and annealing of the solvent [29,30]. Here, some common and effective methods are introduced.…”
Section: Fabrication Of High-quality Perovskite Filmsmentioning
confidence: 99%
“…In order to solve this problem, Bao et al [28] introduced formamidine acetate salt (FAAc) as an additive to optimize both the crystalline quality and the film morphology. By this, highly homogeneous perovskite films with low trap states and uniform morphology could be fabricated.…”
Section: Additivesmentioning
confidence: 99%